Development of a Multimedia Learning Tool by Utilizing Artificial Intelligence (AI) Towards Basic Teaching Skills in Microteaching Courses for Physics Learning - Megalina, Yeni; Rugaya, Rugaya; Amdani, Khairul; Sihombing, Rizky Agassy (Jurnal Penelitian dan Pembelajaran IPA, 2025)
This study aimed to address the challenges encountered by student-teachers during the School Field Introduction Program 2, particularly in classroom management and professional ethics—issues largely attributed to an insufficient understanding of basic teaching skills and core teacher competencies. To overcome these problems, the researchers developed a multimedia-based learning tool designed to enhance student-teachers’ mastery of fundamental teaching skills. The multimedia integrates text, audio, visuals, and teaching simulation videos based on innovative instructional models such as Project-Based Learning (PjBL), and incorporates Artificial Intelligence (AI) using the D-ID platform to generate interactive teaching avatars. The study was conducted in the Physics Education Department at Universitas Negeri Medan, Indonesia, using a Research and Development (R&D) approach following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Both internal and external evaluations were carried out to assess the tool’s feasibility, practicality, and effectiveness. The results indicated that the developed multimedia was highly feasible (expert validation scores exceeding 89%), highly practical (user response score of 86.78%), and moderately effective (N-gain score of 0.57) in improving students’ teaching competencies. It is recommended that microteaching lecturers adopt this multimedia tool to support pre-service teachers in developing professional classroom practices through more interactive and reflective learning.